AN ANALYSIS OF EDUCATIONAL VALUE IN “LIFE OF PI” MOVIE - Tiara Indah Sari; Titik Hardewiyani; Antoni Jamin; Riski Safitri; Lili Perpisa (Tell-us Journal)
Language serves as a tool for communication. For beginners to understand English, utilizing various media is essential. The movie "Life of Pi" is analyzed to highlight the importance of educational values in our lives. This research addresses two main questions: What educational values are present in the "Life of Pi" movie, and what benefits does watching the movie offer? The research methodology used is descriptive qualitative. The study examines the educational values in the "Life of Pi" movie by collecting data through written and oral words, using observation and documentation techniques. The findings reveal several educational values in the "Life of Pi" movie: perseverance (20%), gratitude (15%), spirituality (15%), peace (15%), loyalty (10%), diligence (10%), selflessness (5%), purity (5%), and respect (5%). Additionally, there are three key benefits of watching "Life of Pi": it serves as an educational medium, an entertainment medium, and a source of inspiration